Pengaruh Persepsi Stigma Sosial Dan Dukungan Sosial Terhadap Kesejahteraan Psikologis Pada Narapidana - Wahyu Utami (Journal An-Nafs: Kajian Penelitian Psikologi, 2018)
This study aims to determine the effect of social stigma perception and social support on psychological wellbeing on prisoners. perceptions of social stigma and social support as independent variables and psychological well-being of dependent variables. Subjects were 140 prisoners who underwent half of prisoners in prisons class II A kediri with age range 20 to 37 years. The random sampling technique is used as the subject taking method. Data analysis used multiple linear regression analysis and data collection using scale psychological well being scale (PWBS), perceived social stigmatization (STS) and Multidimensional scale of perceived social support (MSPSS). The results showed that social stigma perception with psychological well-being had negative and significant influence with value (? = -.514, p = 0,000), social support gave influence to psychological welfare with value (? = 0.422, P = 0.000), perception social stigma and social support together have an influence on psychological well-being with value (F = 54,339, P = 0,000)